Preparation method of liquid filtering material with multi-layer interval type continuous gradient structure

By using the skin-core structure of PP resin core layer and PE resin skin layer in the multi-layer non-woven fabric composite, combined with the process of cross-laying, puncture heat baking and multi-roller stretching, the problem of low bonding strength and puncture in the existing technology is solved. hole problem, achieving efficient liquid filtration and extending the service life of the material.

CN119348240AActive Publication Date: 2025-01-24ZHEJIANG SHENGLAN NEW MATERIAL&TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411262858.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

In the prior art, the bonding strength and puncture holes are problematic when composited with multi-layer nonwoven fabrics, resulting in a decrease in surface flatness of the material and a decrease in filtration performance.

Method used

It uses PP resin as the core layer and PE resin as the skin core structure. Through the process of cross-laying, puncture heat baking and multi-roller stretching, the filter monomer made of the dust-holding layer is compounded into a multi-layer spaced continuous gradient. Structural liquid filtration materials. Puncture and heat drying form fiber entanglement points and reinforce them, cross-laying and multi-roller stretching flatten the puncture holes and improve the flatness of the material.

Benefits of technology

It significantly improves the composite strength and flatness of the material, extends the service life of the material, and avoids the problem of early failure of the material surface.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of filter materials, discloses a preparation method of a liquid filter material with a multi-layer interval type continuous gradual change structure, and provides the preparation method of the liquid filter material with the multi-layer interval type continuous gradual change structure. Fibers of a dust containing layer in the method adopt a skin-core structure with PP resin as a core layer and PE resin as a skin layer; according to the method, cross lapping, puncture heat drying and multi-roller stretching are used for compounding filtering monomers made of dust containing layers into the liquid filtering material with the multi-layer interval type continuous gradient structure, and dust containing layer fibers of the filtering monomers can enter the dust containing layers of the adjacent filtering monomers to form fiber entanglement points in the puncture heat drying process; through hot drying, the PE resin of the skin layer can be molten, bonding and reinforcing fiber entanglement points are formed at the fiber entanglement points, the composite strength of the material is remarkably improved, puncture holes generated through puncture can be leveled through cross lapping and multi-roller stretching, the flatness of the surface of the material is improved, and it is guaranteed that the material cannot be remarkably deformed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of filter materials, and in particular to a method for preparing a multi-layer interval type continuous gradient structure liquid filter material. Background Art

[0002] Traditional filter materials are mainly composed of a single-layer filter membrane, but in the actual filtering environment, there are many solid particles in the filter medium, and these solid particles will be intercepted on the filtering side of the filter membrane. The accumulation of these solid particles will lead to lower filtering performance of the filter membrane. At the same time, the solid particles will cause friction on the filtering side of the filter membrane, causing wear of the filter membrane. Therefore, in order to solve the above problems, the prior art adds a pre-filter layer to the filtering side of the filter membrane to intercept the solid particles; currently, the pre-filter layer is mainly composed of a dust-holding layer with a three-dimensional space. The commonly used dust-holding layer is a non-woven fabric made of polyester fiber. Since the non-woven fabric is relatively soft, it is necessary to add a skeleton layer to enable the non-woven fabric to maintain its shape under the filtering pressure to ensure that the non-woven fabric has enough space to accommodate solid particles.

[0003] The amount of solid particles that a non-woven fabric can hold is greatly affected by the wire diameter of the polyester fiber inside the non-woven fabric. The smaller the fiber wire diameter, the larger the dust holding space per unit volume. However, the smaller the fiber wire diameter, the looser the structure of the non-woven fabric, and the thinner the layered structure it can form. Therefore, if you want to have a certain dust holding capacity, you need to stack multiple layers of non-woven fabrics so that their thickness can meet the application standard. For example, a multi-layer melt-blown non-woven fabric and a preparation method thereof disclosed in publication number CN111876905A overlaps multiple layers of non-woven fabrics with different fiber diameters, so that the filter material filters particles of different particle sizes in batches, thereby increasing the dust holding capacity of the filter material.

[0004] At present, in the prior art, point welding, adhesives, needle punching and hydroentanglement are usually used to compound multi-layer non-woven fabrics. Point welding compounding will cause the fibers at the welding points of the dust holding layer to be welded as a whole, destroying the internal space of the welding layer and reducing the dust holding capacity of the dust holding layer. During adhesive compounding, the adhesive will change the fiber diameter of the composite surface and reduce the particle size of filterable solid particles. Needle punching is to use solid needles to make the fibers of the dust holding layer penetrate into the interior of the adjacent non-woven fabrics and form fiber entanglement points in the adjacent non-woven fabrics. Hydroentanglement is to use high-pressure water flow to penetrate the fibers into the interior of the adjacent non-woven fabrics and form fiber entanglement points in the adjacent non-woven fabrics. Fiber entanglement points. Currently, spunlace and needle punching can not significantly damage the internal space of non-woven fabrics, and will not significantly reduce the dust holding capacity of non-woven fabrics. Therefore, in the dust holding layer composite process, needle punching and spunlace are more important than point welding and adhesives. However, the composite strength of needle punching and spunlace is lower than that of point welding and adhesives. In addition, puncture holes will appear on the surface of the material after needling and spunlace. These puncture holes will cause the surface flatness of the material to decrease, and it will be easier to accumulate larger particles at the puncture holes, resulting in faster formation of a dirt accumulation layer on the material surface, which will cause dirt to accumulate on the material surface faster than inside the material, thus causing the entire material to fail. Summary of the invention

[0005] The present invention aims at the problems of low bonding strength and puncture holes in the prior art when compounding multiple dust-holding layers by puncture, and provides a method for preparing a multi-layer interval type continuous gradient structure liquid filter material. The fibers of the dust-holding layer in the method adopt a skin-core structure in which PP resin is the core layer and PE resin is the skin layer. The method uses cross-lamination, puncture hot baking and multi-roller stretching to compound the filter monomers made of the dust-holding layer into a multi-layer interval type continuous gradient structure liquid filter material. During the puncture hot baking, the dust-holding layer fibers of the filter monomer can enter the dust-holding layer of the adjacent filter monomer to form fiber entanglement points. The hot baking can melt the skin layer PE resin and form bonding and reinforcement at the fiber entanglement points to significantly increase the composite strength of the material. The cross-lamination and multi-roller stretching can flatten the puncture holes produced by the puncture, improve the flatness of the material surface and ensure that the material will not be significantly deformed.

[0006] The specific technical scheme of the present invention is: A preparation method of a multi-layer interval type continuous gradient structure liquid filter material, comprising the following steps: spunbonding PP resin and PE resin to form a dust holding layer, melt-blowing PP resin to form a skeleton layer on the surface of the dust holding layer, cold-pressing the skeleton layer and the dust holding layer on the surface of the dust holding layer to form filter monomers, and sequentially cross-laying, puncturing, hot-drying and multi-roller stretching the filter monomers to form a multi-layer liquid filter skeleton material; The fibers of the dust holding layer are a PP resin core layer and a PE resin skin layer; The cross-laying method is that adjacent filter units are overlapped at a staggered angle of 30 to 60 degrees; The tensile strength of the multi-roller stretching is 3 to 8 N / m.

[0007] The present invention provides a method for preparing a multi-layer interval type continuous gradient structure liquid filter material. The method adopts cross-lamination, puncture hot baking and multi-roller stretching to compound multiple layers of filter monomers made of dust holding layers to prepare the multi-layer interval type continuous gradient structure liquid filter material. The puncture hot baking of the method will not significantly change the dust holding capacity of the dust holding layer and can significantly improve the bonding strength of the material. The cross-lamination and multi-roller stretching can flatten the puncture holes formed by puncture to improve the flatness of the material without causing excessive deformation of the material.

[0008] The fiber of the dust holding layer of the present invention has a skin-core structure, wherein the core layer is PP resin and the skin layer is PE resin. When the dust holding layer fiber of the structure is punctured and hot-dried, the puncture will cause the fiber of the dust holding layer of the filter monomer to penetrate into the dust holding layer of the adjacent filter monomer and form a fiber entanglement point. The PE resin skin layer of the dust holding layer fiber can be melted by hot drying, while the internal PP resin core layer will not be deformed. The molten PE resin will form a bond at the fiber entanglement point, thereby reinforcing the fiber entanglement point, thereby significantly improving the bonding strength of the material after puncture and compounding.

[0009] Due to the puncture treatment used in the present invention, puncture holes will be generated on the surface of the material after the puncture treatment. These puncture holes will reduce the flatness of the material surface, making it easier for the material surface to accumulate dirt, causing the material surface to fail faster than the inside of the material. Therefore, the present invention proposes to perform multi-roller stretching on the material after puncture, and the puncture holes on the surface of the material are flattened by multi-roller stretching, thereby improving the flatness of the material surface. However, in actual operation, the present invention finds that after the filter monomers are stacked in the same direction, different structural stresses of the material circumferentially will occur when multi-roller stretching is performed. When the material is stretched along the extension direction, the material is very easy to be stretched and deformed significantly, while when the material is stretched at an angle to the extension direction, the material will not be easily stretched to deformation. Therefore, based on the above characteristics, the present invention proposes a cross-laying stacking method, in which adjacent filter monomers are stacked at an interlaced angle of 30 to 60 degrees. The structural stress of the composite material after stacking is uniform, and when multi-roller stretching is used, the puncture holes on the material can be flattened without significantly changing the deformation amount of the material.

[0010] Preferably, in the spunbond process, the mass fraction of the PP resin is 65 to 75 parts, and the mass fraction of the PE resin is 25 to 35 parts.

[0011] Preferably, in the melt-blowing process: the melt index of the PP resin is 400 to 600 g / min.

[0012] Preferably, the conditions of the melt-blowing process include: the temperature of the screw extruder is 160-170°C.

[0013] Preferably, the conditions of the meltblowing process also include: a meltblowing die temperature of 160-170°C, a hot air temperature of 160-170°C, and an air pressure of 0.1-0.5 MPa.

[0014] Preferably, the temperature of the screw extruder is 160-170°C.

[0015] Preferably, the spinning conditions include: melt-blowing die temperature of 160-170°C, hot air temperature of 160-170°C, wind pressure of 0.1-0.5 MPa, and the skeleton layer weight of 2-5 g / cm 2 The dust holding layer has a gram weight of 5 to 15 g / cm 2 The fiber diameter of the dust holding layer is 2 to 20 μm.

[0016] Preferably, the puncture is one or both of acupuncture and water puncture, and the puncture direction is to insert the needle once perpendicularly with the surface of the material as a plane.

[0017] Preferably, the multi-roller stretching includes circumferential stretching, and the circumferential stretching includes six-equal-division circumferential stretching, eight-equal-division circumferential stretching and twelve-equal-division circumferential stretching.

[0018] Preferably, the temperature of the heat drying is 100-110°C.

[0019] Compared with the prior art, this application has the following technical effects: The invention provides a method for preparing a multi-layer interval type continuous gradient structure liquid filter material. The fibers of the dust holding layer in the method adopt a skin-core structure in which PP resin is a core layer and PE resin is a skin layer. The method uses cross-lamination, puncture hot baking and multi-roller stretching to compound filter monomers made of the dust holding layer into a multi-layer interval type continuous gradient structure liquid filter material. During the puncture hot baking, the dust holding layer fibers of the filter monomer can enter the dust holding layer of the adjacent filter monomer to form fiber entanglement points. The hot baking can melt the skin layer PE resin and form bonding and reinforcement at the fiber entanglement points to significantly increase the composite strength of the material. The cross-lamination and multi-roller stretching can flatten the puncture holes produced by the puncture to improve the flatness of the material surface and ensure that the material will not be significantly deformed. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments.

[0021] Embodiment 1: A multi-layer interval type continuous gradient structure liquid filter material, characterized by comprising the following steps: Step 1: Inject 70 parts of PP resin into a screw extruder (the operating temperature of the screw extruder is 165°C) to make a molten PP resin, and inject 30 parts of PE resin into a screw extruder (the operating temperature of the screw extruder is 120°C) to make a molten PE resin. The molten PP resin and the molten PE resin are respectively input into the spinning box and extruded through a spinneret of a skin-core structure (the skin layer is PE resin, the core layer is PP resin, and the mass ratio of the skin layer to the core layer is 1:6) for melt spinning. The melt spinning is blown, stretched and cooled to form filaments, and the filaments are formed into a dust-holding layer on a web-forming machine through a swinging device (the fiber diameter is 2 to 20 μm, and the gram weight is 10 g / cm 2 ); injecting the second resin (PP resin with a melt index of 400 to 600 g / min) into a screw extruder (the operating temperature of the screw extruder is 165°C) to form a molten second resin, injecting the molten second resin into a melt-blowing device and melt-blowing a skeleton layer (the gram weight of the skeleton layer is 3 g / cm 2 ) is made into a preform, and the melt-blowing conditions are: the melt-blowing die temperature is 165° C., and the hot air temperature is 165° C.; Step 2: The preform obtained in step 1 is subjected to cold pressing treatment (point pressing, pressing point area 8%, rolling speed 4m / min, pressure direction from skeleton layer to dust holding layer) by cold pressing roller (cold pressing roller temperature is 105°C) to prepare a filter monomer; Step three: cross-lay 10 layers of the filter monomers prepared in step two, the cross-laying method is to overlap adjacent filter monomers at a staggered angle of 45°; after overlapping, puncture and heat-dry, the puncture is performed by acupuncture, and the acupuncture direction is to insert the needle vertically from top to bottom once and then from bottom to top once with the surface of the material as the plane. After the acupuncture is completed, place it in a heat drying device at a working temperature of 105°C and heat-dry for 5 minutes. After heat drying, cool it to 70°C and then perform multi-roller stretching. The stretching direction is circumferential eight-division stretching, and the stretching strength is 5N / m. After multi-roller stretching, cool it to room temperature to form a multi-layer interval continuous gradient structure liquid filter material.

[0022] Embodiment 2: A multi-layer interval type continuous gradient structure liquid filter material, characterized by comprising the following steps: Step 1: Inject 65 parts of PP resin into a screw extruder (the operating temperature of the screw extruder is 165°C) to make a molten PP resin, and inject 35 parts of PE resin into a screw extruder (the operating temperature of the screw extruder is 120°C) to make a molten PE resin. The molten PP resin and the molten PE resin are respectively input into the spinning box and extruded through a spinneret of a skin-core structure (the skin layer is PE resin, the core layer is PP resin, and the mass ratio of the skin layer to the core layer is 1:5) for melt spinning. The melt spinning is blown, stretched and cooled to form filaments, and the filaments are formed into a dust-holding layer on a web-forming machine through a swing device (the fiber diameter is 2 to 20 μm, and the gram weight is 5 g / cm2 ); injecting the second resin (PP resin with a melt index of 400 to 600 g / min) into a screw extruder (the operating temperature of the screw extruder is 165°C) to form a molten second resin, injecting the molten second resin into a melt-blowing device and melt-blowing a skeleton layer (the gram weight of the skeleton layer is 2 g / cm 2 ) is made into a preform, and the melt-blowing conditions are: the melt-blowing die temperature is 165° C., and the hot air temperature is 165° C.; Step 2: The preform obtained in step 1 is subjected to cold pressing treatment (point pressing, pressing point area 3%, rolling speed 3m / min, and pressure direction from the skeleton layer to the dust holding layer) by a cold pressing roller (cold pressing roller temperature is 100°C) to form a filter monomer; Step three: cross-lay 10 layers of the filter monomers prepared in step two, the cross-laying method is to overlap adjacent filter monomers at a staggered angle of 30°; after overlapping, puncture and heat-dry, the puncture is performed by acupuncture, and the acupuncture direction is to insert the needle vertically from top to bottom once and then from bottom to top once with the surface of the material as the plane. After the acupuncture is completed, place it in a heat drying device at a working temperature of 100°C and heat-dry for 5 minutes. After heat drying, cool it to 80°C and then perform multi-roller stretching. The stretching direction is circumferential stretching in twelve equal parts, and the stretching strength is 3N / m. After multi-roller stretching, cool it to room temperature to form a multi-layer interval continuous gradient structure liquid filter material.

[0023] Embodiment 3: A multi-layer interval type continuous gradient structure liquid filter material, characterized by comprising the following steps: Step 1: Inject 75 parts of PP resin into a screw extruder (the operating temperature of the screw extruder is 165°C) to make a molten PP resin, and inject 25 parts of PE resin into a screw extruder (the operating temperature of the screw extruder is 120°C) to make a molten PE resin. The molten PP resin and the molten PE resin are respectively input into the spinning box and extruded through a spinneret of a skin-core structure (the skin layer is PE resin, the core layer is PP resin, and the mass ratio of the skin layer to the core layer is 1:7) for melt spinning. The melt spinning is blown, stretched and cooled to form filaments, and the filaments are formed into a dust-holding layer on a web-forming machine through a swing device (the fiber diameter is 2 to 20 μm, and the gram weight is 15 g / cm 2 ); injecting the second resin (PP resin with a melt index of 400 to 600 g / min) into a screw extruder (the operating temperature of the screw extruder is 165°C) to form a molten second resin, injecting the molten second resin into a melt-blowing device and melt-blowing a skeleton layer (the gram weight of the skeleton layer is 5 g / cm 2 ) is made into a preform, and the melt-blowing conditions are: the melt-blowing die temperature is 165° C., and the hot air temperature is 165° C.; Step 2: The preform obtained in step 1 is subjected to cold pressing treatment (point pressing, pressing point area 20%, rolling speed 5m / min, pressure direction from skeleton layer to dust holding layer) by cold pressing roller (cold pressing roller temperature is 110°C) to prepare a filter unit; Step three: cross-laying 10 layers of the filter monomers prepared in step two, the cross-laying method is to overlap adjacent filter monomers at a staggered angle of 60°; after overlapping, puncture and heat drying are performed, and the puncture is performed by acupuncture, and the acupuncture direction is to insert the needle vertically from top to bottom once and then from bottom to top once with the surface of the material as the plane. After the acupuncture is completed, it is placed in a heat drying device with a working temperature of 110°C and heat-dried for 5 minutes. After heat drying, it is cooled to 80°C and then stretched by multiple rollers. The stretching direction is circumferential stretching in six equal parts, and the stretching strength is 8N / m. After multi-roll stretching, it is cooled to room temperature to form a multi-layer interval continuous gradient structure liquid filter material.

[0024] Embodiment 4: A multi-layer interval type continuous gradient structure liquid filter material, characterized by comprising the following steps: Step 1: Inject 70 parts of PP resin into a screw extruder (the operating temperature of the screw extruder is 165°C) to make a molten PP resin, and inject 30 parts of PE resin into a screw extruder (the operating temperature of the screw extruder is 120°C) to make a molten PE resin. The molten PP resin and the molten PE resin are respectively input into the spinning box and extruded through a spinneret of a skin-core structure (the skin layer is PE resin, the core layer is PP resin, and the mass ratio of the skin layer to the core layer is 1:6) for melt spinning. The melt spinning is blown, stretched and cooled to form filaments, and the filaments are formed into a dust-holding layer on a web-forming machine through a swinging device (the fiber diameter is 2 to 20 μm, and the gram weight is 10 g / cm 2 ); injecting the second resin (PP resin with a melt index of 400 to 600 g / min) into a screw extruder (the operating temperature of the screw extruder is 165°C) to form a molten second resin, injecting the molten second resin into a melt-blowing device and melt-blowing a skeleton layer (the gram weight of the skeleton layer is 3 g / cm 2 ) is made into a preform, and the melt-blowing conditions are: the melt-blowing die temperature is 165° C., and the hot air temperature is 165° C.; Step 2: The preform obtained in step 1 is subjected to cold pressing treatment (point pressing, pressing point area 8%, rolling speed 4m / min, pressure direction from skeleton layer to dust holding layer) by cold pressing roller (cold pressing roller temperature is 105°C) to prepare a filter monomer; Step three: cross-lay 10 layers of the filter monomers prepared in step two, the cross-laying method is to overlap adjacent filter monomers at a staggered angle of 45°; after overlapping, puncture and heat-dry, the puncture is performed by water spurting, and the direction of water spurting is to use the surface of the material as a plane to first impact it once with a vertical high-pressure water flow needle from top to bottom and then impact it once with a vertical high-pressure water flow from bottom to top. After water spurting, dry it to room temperature, and then place it in a heat drying device with a working temperature of 105°C for heat drying for 5 minutes. After heat drying, cool it to 70°C and then perform multi-roller stretching. The stretching direction is circumferential eight-division stretching, and the stretching strength is 5N / m. After multi-roller stretching, cool it to room temperature to form a multi-layer interval continuous gradient structure liquid filter material.

[0025] Embodiment 5: A multi-layer interval type continuous gradient structure liquid filter material, characterized by comprising the following steps: Step 1: Inject 70 parts of PP resin into a screw extruder (the operating temperature of the screw extruder is 165°C) to make a molten PP resin, and inject 30 parts of PE resin into a screw extruder (the operating temperature of the screw extruder is 120°C) to make a molten PE resin. The molten PP resin and the molten PE resin are respectively input into the spinning box and extruded through a spinneret of a skin-core structure (the skin layer is PE resin, the core layer is PP resin, and the mass ratio of the skin layer to the core layer is 1:6) for melt spinning. The melt spinning is blown, stretched and cooled to form filaments, and the filaments are formed into a dust-holding layer on a web-forming machine through a swinging device (the fiber diameter is 2 to 20 μm, and the gram weight is 10 g / cm 2 ); injecting the second resin (PP resin with a melt index of 400 to 600 g / min) into a screw extruder (the operating temperature of the screw extruder is 165°C) to form a molten second resin, injecting the molten second resin into a melt-blowing device and melt-blowing a skeleton layer (the gram weight of the skeleton layer is 3 g / cm 2 ) is made into a preform, and the melt-blowing conditions are: the melt-blowing die temperature is 165° C., and the hot air temperature is 165° C.; Step 2: The preform obtained in step 1 is subjected to cold pressing treatment (point pressing, pressing point area 8%, rolling speed 4m / min, pressure direction from skeleton layer to dust holding layer) by cold pressing roller (cold pressing roller temperature is 105°C) to prepare a filter monomer; Step 3: Cross-lay 10 layers of the filter monomers prepared in step 2, and the cross-laying method is that adjacent filter monomers are overlapped at a 45° staggered angle; after overlapping, puncture and heat drying are carried out, and the puncture is carried out by needle puncture and water puncture. The material surface is used as a plane, and a puncture needle is used to vertically puncture once from top to bottom, and a high-pressure water flow is used to vertically impact and puncture once from bottom to top 5 mm near the puncture point line. After puncturing, it is dried to room temperature, and then placed in a heat drying device with a working temperature of 105°C for heat drying for 5 minutes. After heat drying, it is cooled to 70°C and then stretched by multiple rollers. The stretching direction is eight equal parts of the circumference, and the stretching strength is 5N / m. After multi-roll stretching, it is cooled to room temperature to form a multi-layer interval continuous gradient structure liquid filter material.

[0026] Embodiment 6: A multi-layer interval type continuous gradient structure liquid filter material, characterized by comprising the following steps: Step 1: Inject 70 parts of PP resin into a screw extruder (the operating temperature of the screw extruder is 165°C) to make a molten PP resin, and inject 30 parts of PE resin into a screw extruder (the operating temperature of the screw extruder is 120°C) to make a molten PE resin. The molten PP resin and the molten PE resin are respectively input into the spinning box and extruded through a spinneret of a skin-core structure (the skin layer is PE resin, the core layer is PP resin, and the mass ratio of the skin layer to the core layer is 1:6) for melt spinning. The melt spinning is blown, stretched and cooled to form filaments, and the filaments are formed into a dust-holding layer on a web-forming machine through a swinging device (the fiber diameter is 2 to 20 μm, and the gram weight is 10 g / cm 2 ); injecting the second resin (PP resin with a melt index of 400 to 600 g / min) into a screw extruder (the operating temperature of the screw extruder is 165°C) to form a molten second resin, injecting the molten second resin into a melt-blowing device and melt-blowing a skeleton layer (the gram weight of the skeleton layer is 3 g / cm 2 ) is made into a preform, and the melt-blowing conditions are: the melt-blowing die temperature is 165° C., and the hot air temperature is 165° C.; Step 2: The preform obtained in step 1 is subjected to cold pressing treatment (point pressing, pressing point area 8%, rolling speed 4m / min, pressure direction from skeleton layer to dust holding layer) by cold pressing roller (cold pressing roller temperature is 105°C) to prepare a filter monomer; Step 3: Cross-lay 10 layers of the filter monomers prepared in step 2, and the cross-laying method is that adjacent filter monomers are overlapped at a 45° staggered angle; after overlapping, puncture and heat drying are performed, and the puncture is performed by needle punching-hydropunching-needle punching. The surface of the material is used as a plane, and two rows of parallel puncture needles are used to vertically puncture from top to bottom once. At the intervals between the side-by-side puncture holes as the puncture points, high-pressure water flow is used to vertically impact and puncture from bottom to top once. After puncturing, it is dried to room temperature, and then placed in a heat drying device with a working temperature of 105°C for heat drying for 5 minutes. After heat drying, it is cooled to 70°C and then stretched by multiple rollers. The stretching direction is eight equal parts of the circumference, and the stretching strength is 5N / m. After multi-roll stretching, it is cooled to room temperature to form a multi-layer interval type continuous gradient structure liquid filter material.

[0027] Comparative Example 1: Compared with Example 1, in Comparative Example 1, an infrared band hot pressing roller is used to replace the puncture heat drying to compound the multi-layer filter monomer, and the other conditions are the same as those in Example 1.

[0029] Comparative Example 2: Compared with Example 1, in Comparative Example 2, polyolefin hot melt adhesive was used to replace puncture hot baking to compound the multi-layer filter monomer, and the other conditions were the same as those in Example 1.

[0030] Comparative Example 3: Compared with Example 1, cross-laying is not used in Comparative Example 3, and the multi-layer filter monomers are all overlapped along the material extension direction. The other conditions are the same as those in Example 1.

[0031] Comparative Example 4: Compared with Example 1, no multi-roller stretching was performed in Comparative Example 4, and the other conditions were the same as those in Example 1.

[0032] Comparative Example 5: Compared with Example 1, the meltblown layer fiber in Comparative Example 5 is made of a blended resin of PP resin and PE resin, and the other conditions are the same as those of Example 1.

[0033] Test example: The peel strength of the filter monomers prepared in Examples 1 to 6 and Comparative Examples 1 to 8 and the peel strength of the multilayer liquid filter skeleton material, the dust holding life cycle and the material deformation amount of the multilayer liquid filter skeleton material were tested; The dust holding capacity test method refers to "ISO 16889:2008 Hydraulic transmission filters. Evaluation of filter performance using multiple pass method"; The dust holding cycle test method refers to ISO 16889:2008 Hydraulic transmission filters. Evaluation of filter element filtration performance using multiple pass method, which is the time after the test material reaches the maximum dust holding capacity. The peel strength test method refers to GB / T8808-1988 T-type peel strength test method for soft composite plastics. The instrument used for the peel test is XLW (PC) intelligent electronic tensile testing machine. The material deformation test method measures the volume of the material that has not been stretched by multiple rollers, and records the measured value as V1. Then, the volume of the material that has been stretched by multiple rollers is measured, and the measured value is recorded as V2. The deformation is (V2-V1) / V1.

[0034] The test results are shown in Table 1; Table 1 Test results <![CDATA[Peeling strength (N / M 2 )]]> <![CDATA[Dust holding capacity (g / m 2 )]]> Dust holding cycle (min) Material deformation (%) Example 1 8.7 750 980 2.34 Example 2 8.4 708 925 2.85 Example 3 8.2 715 946 2.68 Example 4 8.7 697 825 2.28 Example 5 8.8 684 816 2.37 Example 6 8.8 703 908 2.48 Comparative Example 1 8.9 431 541 / Comparative Example 2 8.1 569 589 / Comparative Example 3 8.8 754 / 6.87 Comparative Example 4 8.7 652 753 / Comparative Example 5 4.5 / / / As shown in Table 1, the glass strength of the multi-layer interval continuous gradient structure liquid filter material provided in Examples 1 to 6 is 8.2 to 8.8 N / M 2 , dust holding capacity is 684~750g / m 2 The dust holding period is 816 to 980 minutes, and the material deformation is 2.34 to 2.85%.

[0035] Comparative Example 1 uses an infrared band hot pressing roller to replace the puncture hot drying to compound the multi-layer filter monomer. The dust holding capacity of Comparative Example 1 is 431g / m 2 , peel strength is 8.9N / M 2 There is no significant difference in the peel strength of the material of Comparative Example 1 compared with Example 1, but the dust holding capacity is significantly reduced. The above results show that the peel strength of the filter material made of multi-layer filter monomers using puncture hot baking in the present invention is equivalent to the peel strength of the filter material made by point welding, but the dust holding capacity is significantly higher than the filter material made by point welding. In addition, through analysis of the internal structure of the material, it is found that the internal spatial structure of the filter material made using the method of the present application will not change significantly. At the same time, the fiber entanglement points formed in the material are bonded under the action of the PE resin surface layer, and the bonding strength of the fiber entanglement points is significantly improved, so that the peel strength of the material can reach the peel strength after point welding compounding.

[0036] Comparative Example 2 does not use polyolefin hot melt adhesive to replace puncture hot baking to compound the multi-layer filter monomer. The dust holding capacity of Comparative Example 2 is 569g / m 2 , peel strength is 8.1N / M 2 Compared with Example 1, the peel strength of Comparative Example 2 is reduced, and the dust holding capacity of Comparative Example 2 is significantly lower than that of Example 1. The above results show that the dust holding capacity and peel strength of the filter material prepared by the puncture hot baking process provided by the present invention are higher than those of the filter material made by adhesive compound, among which the dust holding capacity of the material made by puncture hot baking compound in the present application is significantly higher than that of the filter material made by adhesive compound.

[0037] Cross-lamination is not used in Comparative Example 3. It can be seen from the material deformation results of Comparative Example 3 and Example 1 that the deformation of Example 1 is only 2.34%, while the material deformation of Comparative Example 3 reaches 6.87%. When analyzing the actual operation process, it is found that when the material without cross-lamination is stretched by multiple rollers, the circumferential structural stress of the material is uneven, and the direction of small stress is very easy to be stretched to deformation, while the direction of large stress will not be easily deformed. Therefore, when the puncture hole is to be flattened, there will be a problem of excessive deformation in the direction of the material with small stress. The circumferential structural stress of the material after cross-lamination is relatively uniform, and the puncture hole can be flattened without easy deformation during multi-roller stretching.

[0038] Comparative Example 4 is a case where multi-roller stretching is not performed. From the dust holding period and dust holding capacity results of the materials in Comparative Example 4 and Example 1, it can be seen that the dust holding capacity of the filter material without multi-roller stretching will be reduced, and the dust holding period after one use will also be reduced. After analyzing the above results, it is found that the puncture holes are very easy to accumulate solid particles during filtration, resulting in the material surface quickly forming a dirt covering layer with the puncture holes as the points, thereby causing the material surface to fail first, resulting in a significant decrease in the service life and dust holding capacity of the filter material.

[0039] In Comparative Example 5, the skin-core structure is not adopted but a blended resin of PP resin and PE resin is used. The fibers of the material using the blended resin will undergo severe deformation after puncture and heat drying, resulting in a significant reduction in the overall structure of the material. The fibers of the material are very easy to break, and the peel strength of the material is low, so it cannot be used.

[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a multi-layer interval continuous gradient structure liquid filter material, characterized in that: The following steps are involved: The dust holding layer is prepared by spunbonding process, the skeleton layer is prepared on the surface of the dust holding layer by meltblowing process, the skeleton layer and the dust holding layer are made into filter monomers by cold pressing, and a plurality of filter monomers are cross-laid, punctured, hot-dried and stretched by multiple rollers in sequence to form a multi-layer interval continuous gradient structure liquid filter material; The fibers of the dust holding layer are a PP resin core layer and a PE resin skin layer; The cross-laying method is that adjacent filter units are overlapped at a staggered angle of 30 to 60 degrees; The tensile strength of the multi-roller stretching is 3-8 N / m.

2. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 1, characterized in that: In the spunbond process, the mass fraction of the PP resin is 65-75 parts, and the mass fraction of the PE resin is 25-35 parts.

3. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 1, characterized in that: In the melt-blowing process, the melt index of the PP resin is 400-600 g / min.

4. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 1, characterized in that: The conditions of the melt-blowing process include: the temperature of the screw extruder is 160-170°C.

5. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 1 or 4, characterized in that: The conditions of the meltblowing process also include: meltblowing die temperature 160~170°C, hot air temperature 160~170°C, and air pressure 0.1~0.5 MPa.

6. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 1, characterized in that: The puncture is one or both of acupuncture and water puncture.

7. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 1, characterized in that: The puncture conditions include: inserting the needle once vertically with the surface of the material as a plane.

8. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 1, characterized in that: The multi-roller stretching includes circumferential stretching.

9. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 8, characterized in that: The circumferential stretching includes six equal parts circumferential stretching, eight equal parts circumferential stretching and twelve equal parts circumferential stretching.

10. The method for preparing a multi-layer interval continuous gradient structure liquid filter material according to claim 1, characterized in that: The temperature of the heat drying is 100-110°C.

Citation Information

Patent Citations

  • Multi-layer melt-blown non-woven fabric and preparation method thereof

    CN111876905A

  • SMS many component compound packing material and producing method with same

    CN101205002A

  • Nonwoven filtering medium and preparation method and application thereof

    CN107385683A

  • High strength PE-PP dual component composite filament with skin-core structure and preparation method thereof

    CN107988654A

  • Alternating interval spunlaced nonwoven material and preparation method thereof

    CN108166153A